3(1+x)=2(x-2)

Simple and best practice solution for 3(1+x)=2(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(1+x)=2(x-2) equation:


Simplifying
3(1 + x) = 2(x + -2)
(1 * 3 + x * 3) = 2(x + -2)
(3 + 3x) = 2(x + -2)

Reorder the terms:
3 + 3x = 2(-2 + x)
3 + 3x = (-2 * 2 + x * 2)
3 + 3x = (-4 + 2x)

Solving
3 + 3x = -4 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
3 + 3x + -2x = -4 + 2x + -2x

Combine like terms: 3x + -2x = 1x
3 + 1x = -4 + 2x + -2x

Combine like terms: 2x + -2x = 0
3 + 1x = -4 + 0
3 + 1x = -4

Add '-3' to each side of the equation.
3 + -3 + 1x = -4 + -3

Combine like terms: 3 + -3 = 0
0 + 1x = -4 + -3
1x = -4 + -3

Combine like terms: -4 + -3 = -7
1x = -7

Divide each side by '1'.
x = -7

Simplifying
x = -7

See similar equations:

| 96=454+24h | | m-2=n | | x-10/5-8=5 | | 4x/2+7=21 | | 2m-4=4n | | 0.4a=9.2 | | 80a+a^2=18a | | ((12a^-3b^4c^2)/(-4a^-7b^-2c))^-2 | | 27=(x^2-.4x) | | 3(6x-7)(3x+7)=0 | | 324=h(h+12)(h+3) | | 10x+30=20+11x | | 3(1x)=2(-2) | | 15y=3y+48 | | 9x^2+24xy+16y^2+90x-130y=0 | | B-9/12=-3 | | 1140=8x+11x | | 5(x-6)+3=33 | | 2x^2-4x=-18 | | 2p/3-5=7 | | -5y-3=4y+13 | | 6/5(8x+2)=-36 | | 8x-.5=3 | | 0=x^2-9x+25 | | 4(x+10)=60 | | 1.5=7.5 | | 6z+9-2z=10+3z-3 | | 4d-2=38 | | x(3-x)=70 | | Y=3/8*-9 | | 7d+6=62 | | -30x^6+40x^5-9x^4-48x^3+54x^2=0 |

Equations solver categories